And the Oscar goes to: Death-feigning behavior in Stenocercus squarrosus Nogueira & Rodrigues, 2006 (Squamata, Tropiduridae) - Belo da Silva, Maria Regilane; Antonio de Araujo Filho, João; Joventino Roberto, Igor; Cardozo Ribeiro, Samuel (Herpetologia Brasileira, 2026)
This study provides the first record of thanatosis (death-feigning behavior) in Stenocercus squarrosus, observed during a herpetofaunal inventory in the municipality of Caldeirão Grande do Piauí, state of Piauí, Brazil. Upon detecting the observer’s approach or following a slight touch, the individual rapidly fled approximately 10–15 cm before abruptly dropping to the ground, pressing its body dorsoventrally against the substrate, and extending its limbs alternately along each side of the body. Such a defensive display occurring without direct handling is particularly rare among lizards. This observation contributes novel behavioral information to the natural history of S. squarrosus, a species regarded as both elusive and rare.